Effect of pH and Electrolysis Time on Removal of Reactive Black B dye by Electrochemical Treatment - Manikandan, S.; Saraswathi, R.; Mohammed Siraj Ansari, A. (Asian Journal of Engineering and Applied Technology, 2018)
The electrochemical treatment was an effective technique in dye processing and it can be enforced to remove color from dye solution. An Experimental setup was made for electrochemical treatment of synthetically prepared Reactive Black B dye in batch mode operation using aluminum electrodes. Based on probability the operating parameters such as pH, Concentration, Electrolysis time, Retention time were determined from which the color removal efficiency (CRE) is optimized. The maximum color removal efficiency of Reactive black B dye was achieved at 98.23% for the concentration of 10mg/l.